An introduction to criminal psychology - Durrant, Russil (Routledge, 2012)
Understanding criminal behaviour: an overview -- Juvenile delinquency and developmental theories of crime -- Mental disorder and crime -- Aggression and violence -- Violent offending -- Collective violence -- Sexual offending -- Drugs and crime -- Punishment -- Prevention, rehabilitation, and restorative justice